Work of masonry under the combined action of vertical and horizontal loads: an analysis of experimental studies - Dovzhenko, Oksana; Pohribnyi, Volodymyr; Usenko, Dmytro; Qiniso, Mahlinza (Academic journal Industrial Machine Building Civil Engineering, 2020)
The characteristic damage of masonry walls under the combined action of vertical and horizontal loads has been analyzed. Possible schemes of masonry destruction are considered. A diagonal shear is identified as a typical case of the destruction of piers under seismic impacts. The closeness of the loading conditions of the piers of the bearing walls under the action of the seismic force to those that arise in the frame when it is skewed is noted. The article considers the results of experimental studies of masonry specimens on the skew as models of the operation of piers under seismic impacts. The nature of destruction is analyzed, determining factors of influence. Based on the analysis of known experiments, proposals are presented for a kinematically possible scheme for the destruction of masonry walls, which is proposed as a base for the calculation
Keywords: diagonal shear; damage; seismic influences; schemes of destruction